Binge-eating disorder in the Swedish national registers: Somatic comorbidity - Thornton, L.; Watson, Hunna; Jangmo, A.; Welch, E.; Wiklund, C.; von Hausswolff-Juhlin, Y.; Norring, C.; Herman, B.; Larsson, H.; Bulik, C. (John Wiley & Sons, Inc., 2017)
Objective To evaluate associations between binge-eating disorder (BED) and somatic illnesses and determine whether medical comorbidities are more common in individuals who present with BED and comorbid obesity. Method Cases (n = 850) were individuals with a BED diagnosis in the Swedish eating disorders quality registers. Ten community controls were matched to each case on sex, and year, month, and county of birth. Associations of BED status with neurologic, immune, respiratory, gastrointestinal, skin, musculoskeletal, genitourinary, circulatory, and endocrine system diseases were evaluated using conditional logistic regression models. We further examined these associations by adjusting for lifetime psychiatric comorbidity. Amongst individuals with BED, we explored whether comorbid obesity was associated with risk of somatic disorders. Results BED was associated with most classes of diseases evaluated; strongest associations were with diabetes [odds ratio (95% confidence interval) = 5.7 (3.8; 8.7)] and circulatory systems [1.9 (1.3; 2.7)], likely indexing components of metabolic syndrome. Amongst individuals with BED, those with comorbid obesity were more likely to have a lifetime history of respiratory [1.5 (1.1; 2.1)] and gastrointestinal [2.6 (1.7; 4.1)] diseases than those without comorbid obesity. Increased risk of some somatic disease classes in individuals with BED was not simply due to obesity or other lifetime psychiatric comorbidity. Discussion The association of BED with many somatic illnesses highlights the morbidity experienced by individuals with BED. Clinicians treating patients with BED should be vigilant for medical comorbidities. Nonpsychiatric providers may be the first clinical contact for those with BED underscoring the importance of screening in primary care. © 2016 The Authors International Journal of Eating Disorders Published by Wiley Periodicals, Inc. (Int J Eat Disord 2017; 50:58–65)